A6.6 In RA patients, antibodies to the citrullinated peptide EBNA35-58Cit from epstein-barr nuclear antigen-1 crossreact with the citrullinated fibrin peptide β60-74Cit60, 72, 74. (31st January 2014) - Cornillet, M; Verrouil, E; Cantagrel, A; Serre, G; Nogueira, L
Abstract : Background: Among the Rheumatoid Arthritis (RA)-specific antibodies to citrullinated proteins/peptides (ACPA), the autoantibodies to citrullinated fibrinogen (AhFibA) target 2 immunodominant epitopes borne by the peptides α36-50Cit38, 42 and β60-74Cit 60, 72, 74 . RA sera also contain antibodies to the citrullinated peptide EBNA35-58Cit derived from EBNA-1, a protein of Epstein Barr Virus (EBV). Objectives: To analyse the diagnostic value of anti-EBNA35-58Cit antibodies and their relationships with AhFibA, anti-α36-50Cit38, 42 and anti-β60-74Cit60, 72, 74 autoantibodies. Methods: A large representative series of 181 established RA and 436 non-RA rheumatic diseases was tested by ELISA for AhFibA, anti-CCP2, anti-α36-50Cit38, 42, anti-β60-74Cit60, 72, 74 and anti-EBNA35-58Cit antibodies. Diagnostic indexes, correlations and concordances between tests were analysed. In addition, cross-reactivity of anti-EBNA35-58Cit toward β60-74Cit60, 72, 74 and α36-50Cit38, 42 was evaluated in competition assays. Results: At a diagnostic specificity of 98.5%, the diagnostic sensitivity of anti-EBNA35-58Cit antibodies was 36%, similar to that of anti-α36-50Cit38, 42 (41%) but significantly lower than that of anti-β60-74Cit60, 72, 74 (62%) autoantibodies. Moreover, almost all sera containing anti-EBNA35-58 antibodies were reactive to citrullinated fibrinogen, 91% to β60-74Cit60, 72, 74, and 43% to α36-50Cit38, 42 . Anti-EBNA35-58 antibodies titres significantly correlated with those of anti-β60-74Cit60, 72, 74 (r = 0.482), AhFibA (r = 0.504) and anti-CCP2 (r = 0.479) but not with those of anti-α36-50Cit38, 42 (r = 0.051). Competition assays revealed that anti-EBNA35-58Cit antibodies are highly crossreactive with anti-β60-74Cit60, 72, 74 but not with anti-α36-50Cit38, 42 autoantibodies. Conclusions: Anti-EBNA35-58Cit antibodies are present in 36% of AhFibA-positive patients with established RA. They are highly crossreactive with the autoantibodies to the immunodominant fibrin peptide β60-74Cit60, 72, 74. That suggests that the two antibodies have the same fine specificity and therefore correspond to a same subpopulation of ACPA.